2013
DOI: 10.1353/jda.2013.0011
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the Labor Supply in Latin America, 2000–2008

Abstract: This paper analyzes the determinants of participation in the labor supply in a sample of ten Latin American countries. To this end, a VAR model is estimated with the variables economic growth, wages, unemployment and participation rate. A first section discusses the evolution and determining variables of participation rates in the Latin American countries, under the light of recent theories. This is followed by a review of recent literature on participation in Latin American countries. Next, impulse response f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Figure 9 constructed with a cross-section of 2017 data of Latin American countries, shows that as the human opportunity index, IOH, increases, the ratio of female to male employment increases; in other words, investments in health, education, housing, and electricity, that serve girls and children regardless of their parents' income and their place of residence, is a means to promote social mobility and female participation. Caceres (2013) has shown that in Latin American countries the human opportunity index increases with the increase in social spending, particularly spending on education. This highlights the role of social policy in increasing economic growth and external solvency, which indicates that social policy must receive the same, or more, attention than that given to traditional macroeconomic policies.…”
Section: How To Increase the Female To Male Employment Ratiomentioning
confidence: 99%
“…Figure 9 constructed with a cross-section of 2017 data of Latin American countries, shows that as the human opportunity index, IOH, increases, the ratio of female to male employment increases; in other words, investments in health, education, housing, and electricity, that serve girls and children regardless of their parents' income and their place of residence, is a means to promote social mobility and female participation. Caceres (2013) has shown that in Latin American countries the human opportunity index increases with the increase in social spending, particularly spending on education. This highlights the role of social policy in increasing economic growth and external solvency, which indicates that social policy must receive the same, or more, attention than that given to traditional macroeconomic policies.…”
Section: How To Increase the Female To Male Employment Ratiomentioning
confidence: 99%